The Role Of Traditional Institutions In Supporting Food Security Of Small Island Communities - Hidrawati, Hidrawati; Rianse, Usman; Iswandi, R. Marsuki; Arafah, Nur; Hamzah, Awaluddin; Harviyaddin, Harviyaddin (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Traditional institutions function to regulate the order of community lives in the political, economic, socio-cultural, and security fields. This study aims to describe the structure of traditional institutions and explain the role of these institutions in supporting food security for small island communities. The research was carried out in April-December 2021 in the Islands of Wakatobi Regency, Southeast Sulawesi Province, Indonesia. Data were collected through observation, interviews, and literature study with the data triangulation method and analyzed qualitatively. The results show that traditional institutions such as Sara Liya on Wangi-Wangi Island and Sarano Wali on Binongko Island have a management structure that is directly responsible for the community's food security system. Sara plays a role as the person in charge of community welfare, regulates the control and management of agricultural/fishery land, organizes rituals to maintain the stability of food production, and regulates the distribution system and food consumption. Based on the results of this study, it is recommended that the community continue to trust Sara as a traditional institution that can partner with the government. Sara's management is expected to have high adaptability to changing community conditions while still maintaining the values of local wisdom. In addition, the government is expected to provide support for strengthening customary institutions